應用敘事文本於師資培育移民教育課程及其對職前教師跨文化理解之影響 Implement Narrative Inquiry to Immigration Education and Explore Cross-cultural Understanding of Student Teachers - 黃淑玲 Shu-Ling Huang (Higher Education Foundation, 2015)
自1990年代起，我國新住民子女人數逐漸增加，新住民子女已成為教室中的重要群體之一。面對學校中日趨多元化的教室生態，教師需具有跨文化理解能力，師資培育課程亦需回應臺灣社會國際化與學校成員多元化的社會結構。職是之故，本研究以新住民教育為主題，以敘事探究方法，對20位新住民的生命經驗及10 位新住民子女的學校教師進行生命故事訪談，並撰寫成敘事文本，同時應用此敘事課程文本於師資培育之移民教育課程中，並以跨文化理解的教學模式實施課程。師資生於參與敘事探究課程前多數抱持著社會病理觀，視新住民為「局外人」；師資生以敘事探究進行跨文化理解與溝通課程後，進一步理解新住民經驗與自我在歷史、社會與文化深層結構與脈絡中的形成與轉變，師資生對新住民及其子女的理解也轉為文化平等觀，視新住民為「局內人」，尊重他們與主流文化的差異，認為所有的文化皆有其價值與意義。本研究建議身為傳遞知識與文化角色的新一代教師，在臺灣面對多元社會的情境下，需瞭解自己文化的獨特性，以及重新再省思自我的文化價值觀，同時能對不同的文化產生包容、理解、欣賞之態度，並有能力教導學生此觀念，以能成為多元文化教育的領航者。 Since 1990s, the number of new immigrants' children has increased gradually. Children of immigrants have become one of the important ethnic groups in the classroom. Under this multicultural circumstances, teachers should develop their crosscultural understanding. Furthermore, the curriculum for teacher education should be designed to response the social construction of internationalization in Taiwan society and diversification of school members. This study focuses on immigration education and proceeds field interview with 20 new immigrants and 10 school teachers for children of new immigrants. By means of narrative inquiry, this study uses the immigrants' life experiences to write narrative texts which are applied to the curriculum of immigration education in teacher education subsequently. The teaching mode of cross-cultural understanding is implemented in the curriculum as well. Before participating in the curriculum of narrative inquiry, most student teachers view new immigrants as outsiders with sociological-pathological perspectives. With the cross-cultural understanding and communicative curriculum of narrative inquiry, student teachers start to comprehend immigrants' experiences and the process of their ego formation and transformation in the historical, social and cultural construction and context. Instead of the previous negative attitude, student teachers look upon new immigrants as insiders with the concept of egalitarian model of culture. They realize all cultures have their own values and meanings, and know how to respect differences between new immigrants' cultures and mainstream culture. This study suggests that as the giver of knowledge and culture in the multicultural Taiwan society, it is necessary for teachers to understand the unique of their own culture and reflect their values on the culture. Simultaneously, teachers should keep the attitude of tolerance, understanding, appreciation toward different cultures and be capable of teaching their student these perspectives to be pioneers in the field of the multicultural education.